The Depiction of the Grotesque in "He" by Katherine Anne Porter and "The Life You Save May Be Your Own" by Flannery O´Connor - Kopová, Jana (Univerzita Pardubice, 2024)
This bachelor thesis investigates the depiction of the grotesque and its relation to handicap in two short stories "The Life You Save May Be Your Own" written by Mary Flannery O'Connor and "He" by Katherine Anne Porter. The paper attempts to identify the influence the child's handicap has on its mother and how she takes care of the child. The paper also attempts to characterize the literary phenomenon American Southern Renaissance in literary and cultural context.
Vyobrazení groteskna v dílech „He“ od Katherine Anne Porter a „The Life You Save May Be Your Own“ od Flannery O'Connor
Keywords: literatura; rodina; handicap; americká jižanská renesance; groteskno; hlavní postava; O'Connor, Mary Flannery; Porter, Katherine Anne; The Life You Save May Be Your Own; He; literature; family; handicap; American Southern Renaissance; grotesque; protagonist; O'Connor, Mary Flannery; Porter, Katherine Anne; The Life You Save May Be Your Own; He